Quantifying NAFTA environmental impacts: Energy and agriculture - Gloria Soto Montes de Oca (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2008)
After fifteen years, NAFTA has been subject to many evaluations from different perspectives, including environmental assessments. According to the Commission for Environmental Cooperation (CEC), results of these evaluations show that, at the aggregate level, the environmental impacts of free trade are marginal (CEC 2004). The main sectors analyzed have been energy, agriculture, manufacturing and international transportation. In these sectors, the CEC concludes that results only indicate a concentration of some environmental impacts in specific regions, and the presence of peaks in certain key environmental indicators (CEC 2002). In this paper I argue that environmental impacts might seem marginal because although these were identified, several have been hardly quantified.
Keywords: 330; Test; Wirtschaftsintegration; Handelsregionalismus; Umweltbelastung; Energiekonsum; Landwirtschaft; Wohlfahrtseffekt; Messung